Uncivil youth : race, activism, and affirmative governmentality - Kwon, Soo Ah, 1973- (Duke University Press, 2013)
Soo Ah Kwon explores youth of color activism, focusing on the political conditions that enable-and limit-youth of color from achieving meaningful change given the entrenchment of nonprofits within the logic of the neoliberal state.